Closing the Gender Gap: Promoting Labour Market Participation - Jorgen M. Harris; Eleonora Patacchini (Institute of Labor Economics (IZA), 2024)
In many countries, a significant share of the gender earnings gap stems not only from firm's practices, or self-selection into lower productivity jobs, but also from a lower participation among women. Inactivity around the age of motherhood is frequent including in the most advanced countries, and can have lasting consequences on the chances to return to the labor market, as well as future earnings and promotions. In this paper, we discuss the major barriers reducing women's labor force participation and examine the effects of several policies aimed at overcoming those barriers: parental leave, reserved paternal leave, state-funded childcare for young children, extended school hours, and individual taxation. For each, we provide a brief discussion of policy design and effectiveness.
Keywords: J16; J13; J22; 330; economics of gender; child care; time allocation and labor supply; labor market policy; maternal and paternal labor force participation; gender norms